The First Isolation and Molecular Characterization of Shiga Toxin-Producing Virulent Multi-Drug Resistant Atypical Enteropathogenic Escherichia coli O177 Serogroup From South African Cattle - Montso, Peter Kotsoana; Mlambo, Victor; Ateba, Collins Njie (Frontiers in Cellular and Infection Microbiology, 2019)
Atypical enteropathogenic E. coli (aEPEC) is a group of diarrhoeagenic Escherichia coli with high diversity of serogroups, which lack the bundle-forming pili (BFP) and genes encoding for shiga toxins. The aim of this study was to isolate, identify and determine virulence and antibiotic resistance profiles of aEPEC O177 strains from cattle feces. A total of 780 samples were collected from beef and dairy cattle and analyzed for the presence of E. coli O177. One thousand two hundred and seventy-two (1272) presumptive isolates were obtained and 915 were confirmed as E. coli species. Three hundred and seventy-six isolates were positively confirmed as E. coli O177 through amplification of rmlB and wzy gene sequences using multiplex PCR. None of these isolates harbored bfpA gene. A larger proportion (12.74%) of the isolates harbored hlyA gene while 11.20, 9.07, 7.25, 2.60, and 0.63% possessed stx2, stx1, eaeA, stx2a, and stx2d, respectively. Most of E. coli O177 isolates carried stx2/hlyA (9.74%). Furthermore, 7.40% of the isolates harbored stx1/stx2 while 7.09% possessed stx1/stx2/hlyA genes. Only one isolate harbored stx1/stx2/hly/eaeA/stx2a/stx2d while 5.11% of the isolates harbored all the four major virulence genes stx1/stx2/hlyA/eaeA, simultaneously. Further analysis revealed that the isolates displayed varied antimicrobial resistance to erythromycin (63.84%), ampicillin (21.54%), tetracycline (13.37%), streptomycin (17.01%), kanamycin (2.42%), chloramphenicol (1.97%), and norfloxacin (1.40%). Moreover, 20.7% of the isolates exhibited different phenotypic multi-drug resistance patterns. All 73 isolates harbored at least one antimicrobial resistance gene. The aadA, streA, streB, erm, and tetA resistance genes were detected separately and/or concurrently. In conclusion, our findings indicate that environmental isolates of aEPEC O177 strains obtained from cattle in South Africa harbored virulence and antimicrobial resistance gene determinants similar to those reported in other shiga-toxin producing E. coli strains and suggest that these determinants may contribute to the virulence of the isolates.